A novel protection and control strategy for high–voltage power frequency control system. (13th March 2012) - Qing, Xiong; Zhe, Zhang; Xianggen, Yin
The complicated structure and high power density make the protection and control of high voltage power frequency control system difficult. This paper proposed the novel protection and control strategy covered different parts of the system. Taking advantage of microprocessor protection system realised the system–level protection covered the fault of rectifier input, DC link, inverter output and even the induction motor. Improve the main circuit to strengthen security and stability in device level. The paper also analysed the cooperation of the protective trip and PWM pulse blocking and validated the feasibility of dual breaker setting to restrain feedback energy.